“Guys Don’t Have Breasts”: The Lived Experience of Men Who Have BRCA Gene Mutations and Are at Risk for Male Breast Cancer - Skop, Michelle (Am J Mens Health, 2018)
Men with BRCA1 or BRCA2 gene mutations are at increased risk of developing breast cancer and may have an indication for breast cancer screening using mammography. Since breast cancer is often viewed as a woman’s disease, visibilizing and understanding men’s experience of having a BRCA mutation and specifically, of screening for breast cancer through mammography, were the objectives of this research study. The theoretical framework of interpretive phenomenology guided the process of data collection, coding, and analysis. Phenomenology is both a philosophy and research method which focuses on understanding the nature of experience from the perspectives of people experiencing a phenomenon, the essence of and commonalities among people’s experiences, and the ways in which people experience the world through their bodies. Data were collected via in-depth interviews with a purposive sample of 15 male participants recruited from the Male Oncology Research and Education (MORE) Program. This article reports findings about participants’ use of gender-specific language to describe their breasts, awareness of the ways in which their bodies changed overtime, and experiences of undergoing mammograms. This study is the first to describe men with BRCA’s perceptions of their breasts and experiences of mammography in a high-risk cancer screening clinic. This study sheds light on an under-researched area—breasts and masculinities—and could potentially lead to improved clinical understanding of men’s embodied experiences of BRCA, as well as suggestions for improving the delivery of male breast cancer screening services.